SEMI QUANTITATIVE AND QUANTITATIVE ANALYSIS OF ROCKSLIDES AT PONOROGO - PACITAN ROAD KM 226 - Retno Puspa Rini; Arief Rachmansyah; Eko Andi Suryo (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2022)
Rock avalanches is one of the problems that is often faced along the Ponorogo - Pacitan road. The research location was at KM 226 which is located at coordinates 111°22'14.39